Legal Disputes of Emigrant Periodical Publishers from the End of the 19th Century to 1904 - Misiūnas, Remigijus (Knygotyra, 2024)
The subject of the article is the formation of legal dispute practices among Lithuanian emigrant periodical publishers in the USA during the late 19th and early 20th centuries. The aim is to analyze the legal cases brought against emigrant periodical publishers during this period, assessing their causes, aspects of the cases, their coverage in the press, and their consequences, based on scientific research and contemporary press publications. The main focus is on the 1897 case against the newspaper “Saulė” published in Mahanoy City, Pa., where publisher D. T. Bačkauskas was accused of violating a US postal ban by distributing immoral literature. Other notable cases include the 1898–1900 litigation involving Chicago newspaper “Lietuva” publisher A. Olšauskas and editor J. Šernas against local Lithuanian priest A. Kriaučiūnas over critical articles directed at him, and the lawsuit of Shenandoah, Pa. newspaper “Viltis” publisher V. Šlekys by A. Savickas, who accused the newspaper of defamation and demanded the disclosure of the article author’s name.The analysis of these and other cases from the period revealed that litigation was one of many manifestations of the ideological split within the emigrant community in the late 19th and early 20th centuries. As the role of the press grew within the community, clergy, who constituted the majority of the right-wing leadership, found themselves losing the unchallenged authority they had in Lithuania and were unable to compensate for it through their own press and polemics against other factions. Therefore, they tried to exploit legal opportunities. The case against “Saulė” can be partially explained by its popularity within the emigrant community and its occasional positioning as a Catholic newspaper, which drew readers away from the still-weak right-wing press. Priest Kriaučiūnas’s struggle against “Lietuva” can be partly explained by his aim to undermine the influence of the liberal “Lietuva” on Chicago Lithuanians and to create favourable conditions for his newspaper “Katalikas” and its growing influence.Evaluating the causes of the cases, it is possible to discuss the complicated perception of the satirical genre within the emigrant community of that time. On one hand, the hyperbolization of problems and ills in the emigrant life attracted readers with engaging texts, but on the other, it was interpreted as propaganda for a dissolute lifestyle and rejection of religious norms, dismissing the satirical aspect. Additionally, the defense of freedom of speech became a cornerstone in the litigation between Olšauskas and priest Kriaučiūnas. Meanwhile, in the case of Šlekys, the journalistic principle of source protection and the willingness to defend it in court is noteworthy.Regarding the coverage of the cases in the press, e.g. Bačkauskas utilized the reporting of his case in “Saulė” to strengthen his image as an independent publisher and defender of Lithuanian identity. Conversely, the press opposing “Saulė” presented the case as a matter of great significance, serving Lithuanian interests, and depicted the initiator of the case almost as a hero sacrificing for the good of the emigrant community, using colourful epithets and emotional expressions (similar to “Saulė”). The fight for community interests and justice was echoed in the descriptions of the cases of Olšauskas and priest Kriaučiūnas.Moreover, during the analyzed period, there emerged an understanding among individuals who considered themselves defamed in the press that their grievances could be addressed legally. It can be said that this became part of the rapidly forming tradition within the emigrant community to resolve even the smallest quarrels through legal means, despite contemporaries’ concerns that three things tarnished the Lithuanian name in the eyes of others: drunkenness, brawling, and lawsuits, worrying about how much money was wasted and how much of it went to non-Lithuanians. This tradition became customary in the emigrant community, and legal disputes among periodical publishers became not an exceptional occurrence but a common practice, sometimes resolving ideological disagreements in court, throughout the 20th century.
Keywords: Lithuanian emigrants; emigrant periodical publishing in the USA; legal disputes of periodical publishers